Assessment of Perinatal Mortality in a Tertiary Care Hospital by Using Wigglesworth Classification - Begum, Lutfun Nahar; Azad, Kishwar; Akhter, Shahida; Nahar, Nazmun; Abdullah, Abu Hasan Md (Bangladesh Journal of Child Health, 2010)
Objective: To determine the causes of perinatal death using Wigglesworth classification and to assess the feasibility of using Wigglesworth classification in a tertiary care hospital setting. Methods: All live and stillborn babies delivered at BIRDEM over a 5 yr period(from January 2000 to December 2004) were recorded. Perinatal deaths of that period were analysed according to Wigglesworth classification Results: According to Wigglesworth classification, majority of deaths were in the group "macerated stillbirths" (63.5%). Perinatal asphyxia was responsible for 13.6% of deaths, lethal congenital malformation was found in 11.2% and immaturity and "others" each accounted for 6.1%. Conclusion: Macerated stillbirth and asphyxia were the two leading causes of death at BIRDEM and Wigglesworth classification has been found to be feasible in BIRDEM for categorising perinatal deaths retrospectively. Key words: Perinatal death; Wigglesworth classification DOI: 10.3329/bjch.v31i1.6072 Bangladesh Journal of Child Health 2007; Vol.31(1-3): 32-39